If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -128 = 3x Reorder the terms: -128 + X = 3x Solving -128 + X = 3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '128' to each side of the equation. -128 + 128 + X = 128 + 3x Combine like terms: -128 + 128 = 0 0 + X = 128 + 3x X = 128 + 3x Simplifying X = 128 + 3x
| 6y=10+4y | | 8x-4= | | 4(x-7)=2x-6 | | 30=6(3a+2b) | | 2g+2(-5+3g)=1-g | | -14+r=23 | | 14539=5431+396t | | 3x-5=2(2x+5) | | x+-8=9 | | 42=6(3a+2b) | | 7t-4=24 | | 3x-5=(2x+5) | | 2x+10=-34 | | 5(2z-2)=9(z+5) | | 4k-9k=10 | | 3*2-7y=17 | | 3*0-7y=17 | | 3*-2-7y=17 | | 6j+5j=33 | | 4+x=-4+x+x | | 3(x-50)=2(x+5) | | 8(-4)+(-1)(6)-(-2)(4)= | | 6+6x=7x+2 | | -8+2a=-8 | | 9-n=12 | | .8s=-128 | | 3y+2=26 | | 64y=7(9y-3) | | 53=x-5x+9 | | 33-[3+6y-4(y+3)]=-4(5y-5)-[5(y-1)-19y+11] | | 5x-4y=24 | | 15q-17=13 |